Understanding the difference in beef quality between Angus and Nellore cattle through a proteomic and phosphoproteomic approach - Rodrigues, Rafael Torres de Souza (2016)
Proteins are the major constituents of muscle and are key molecules regulating the metabolic changes during conversion of muscle to meat. Brazil is one of the largest exporters of beef and most of the Brazilian cattle are composed by zebu (Nellore) genotype. Zebu beef is generally leaner and tougher than taurine. The aim of this study was to compare the muscle proteomic and phosphoproteomic profile of Nellore and Angus. Seven animals of each breed previously subjected to the same growth management were confined for 84 days. Proteins were extracted from Logissimus dorsi samples collected immediately after slaughter and separated by two-dimensional electrophoresis. Pro-Q Diamond stain was used in phosphoproteomics. Proteins identification was performed using matrix assisted laser desorption/ionization time-of-flight mass spectrometry. Tropomyosin alpha-1 chain, troponin-T, myosin light chain-1 fragment, cytoplasmic malate dehydrogenase, alpha-enolase and 78 kDa glucose-regulated protein were more abundant in Nellore, while myosin light chain 3, prohibitin, mitochondrial stress-70 protein and heat shock 70 kDa protein 6 were more abundant in Angus (P<0.05). Nellore had higher phosphorylation of myosin regulatory light chain-2, alpha actin-1, triosephosphate isomerase and 14-3-3 protein epsilon. However, Angus had greater phosphorylation of phosphoglucomutase-1 and troponin-T (P<0.05). Therefore, proteins involved in contraction and muscle organization, and heat shock proteins related to cell flux of calcium and apoptosis might be associated with differences in beef tenderness between Angus and Nellore. Furthermore, prohibitin might be linked to differences in intramuscular fat. Additionally, differences in phosphorylation of myofilaments and glycolytic enzymes could be involved with differences in muscle contraction force, susceptibility to calpain, apoptosis and postmortem glycolysis, which might also be related to differences in beef tenderness among Angus and Nellore.